Identification of Halophilic Microbes in Lung Fibrotic Tissue by Oligotyping - D’Alessandro-Gabazza, Corina N.; Méndez-García, Celia; Hataji, Osamu; Westergaard, Sara; Watanabe, Fumiaki; Yasuma, Taro; Toda, Masaaki; Fujimoto, Hajime; Nishihama, Kota; Fujiwara, Kentaro; Taguchi, Osamu; Kobayashi, Tetsu; et al. (Frontiers in Microbiology, 2018)
Idiopathic pulmonary fibrosis is an incurable disease with poor prognosis and unknown etiology. The poor clinical outcome is associated with enhanced microbial burden in bronchoalveolar lavage fluid from idiopathic pulmonary fibrosis patients. However, whether microbes from the respiratory tract fluid cause the disease remains uncertain. Tissue-associated microbes can influence host physiology in health and disease development. The aim of this study was to evaluate the existence of microbes in lung fibrotic tissues. We evaluated the microbial community in lung tissues from idiopathic pulmonary fibrosis and from human transforming growth factor-beta1 transgenic mice with lung fibrosis by oligotyping. We also evaluated the microbial population in non-tumor-bearing tissues from surgical specimens of lung cancer patients. The phyla Firmicutes and the genus Clostridium tended to be predominant in the lung tissue from idiopathic pulmonary fibrosis and lung cancer patients. Oligotyping analysis revealed a predominance of bacteria belonging to the genera Halomonas, Shewanella, Christensenella and Clostridium in lung tissue from idiopathic pulmonary fibrosis and lung cancer. Evaluation of the microbial community in the lung tissue from mice revealed abundance of Proteobacteria in both wild-type littermates and transgenic mice. However, the genus Halomonas tended to be more abundant in transforming growth factor-beta1 transgenic mice compared to wild-type mice. In conclusion, this study describes tissue-associated microbes in lung fibrotic tissues from idiopathic pulmonary fibrosis patients and from aging transforming growth factor-beta1 transgenic mice.